2006
DOI: 10.3998/ark.5550190.0007.603
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic approaches towards a new class of strained "lactenediynes"

Abstract: The paper described two alternative synthetic approaches towards a new class of strained "lactenediynes", compounds where a 10-membered enediyne ring is fused with a β-lactam. Although the two alternative syntheses were successful up to the last step, the cyclization to give the desired products failed in both cases, probably because of excessive steric strain in the products. In one of the two approaches (which was the most efficient one in terms of overall yield) a mixture of diastereoisomeric cyclodimers wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…These imines have been used as substrate in nucleophilic 1,2- or 1,4-additions . A limited number of Staudinger [2 + 2] cycloadditions are known. , Metal-catalyzed cycloisomerizations and hydrocarbonylations leading to nitrogen-containing heterocycles have been explored recently. To the best of our knowledge, only one article, dealing with cyclotrimerization, mentions the reactivity of their dicobalt hexacarbonyl complexes …”
Section: Introductionmentioning
confidence: 99%
“…These imines have been used as substrate in nucleophilic 1,2- or 1,4-additions . A limited number of Staudinger [2 + 2] cycloadditions are known. , Metal-catalyzed cycloisomerizations and hydrocarbonylations leading to nitrogen-containing heterocycles have been explored recently. To the best of our knowledge, only one article, dealing with cyclotrimerization, mentions the reactivity of their dicobalt hexacarbonyl complexes …”
Section: Introductionmentioning
confidence: 99%
“…A few months after the publication of the propargyl sulfone work, Banfi and Guanti reported the first synthesis of β-lactam-fused enediynes 4.076 and 4.077 . They have elegantly demonstrated that the β-lactam ring can act as a locking device to stabilize the otherwise unstable 10-membered enediyne system. Opening of the β-lactam ring unlocked the system, which enabled it to undergo BC.…”
Section: 2 Category 2:  Activation Through Acid- or Base-catalyzed Ri...mentioning
confidence: 99%
“…Because of the importance of these enediynes, it is pertinent to briefly mention their synthesis in this review. In Banfi's method, the key step is an intramolecular addition of acetylene to an aldehyde involving the Nozaki reaction 80 (Scheme ).
21 Nozaki Reaction Route to Azetidinyl Enediyne (Banfi and Guanti) a a (a) Pd(PhCN) 2 Cl 2 , CuI, piperidine, THF; (b) (i) AgNO 3 , KCN; (ii) I 2 , morpholine, benzene, rt; (iii) (COCl) 2 , DMSO, NEt 3 , CH 2 Cl 2 ; and (c) CrCl 2 , NiCl 2 (cat.
…”
Section: 2 Category 2:  Activation Through Acid- or Base-catalyzed Ri...mentioning
confidence: 99%
“…More recently we have carried out two alternative approaches to structures (42). 23 In both cases, however, the final cyclization step failed to provide the desired monomer. In one case we could isolate various stereoisomeric cyclodimers.…”
Section: Figurementioning
confidence: 99%